Study of Organizational Behavior for Afghanistan's State Development: An Applied Evaluation of Robbins Theories - Dadman, Enayatullah; Amainzai , Wafiullah (HISTORICAL: Journal of History and Social Sciences, 2025)
This research explores the impact of organizational behavior on Afghanistan’s state development by applying Stephen P. Robbins’ theories to assess institutional challenges and propose strategic solutions. Afghanistan’s governance structures suffer from weak leadership, ineffective communication, low motivation, and poor organizational culture, all of which hinder institutional performance and state-building efforts. Utilizing a qualitative research methodology, this study relies on literature and book sources to analyze Robbins’ key concepts, including motivation, leadership, decision-making, and organizational culture, within the Afghan context. The findings reveal that inefficient organizational structures, lack of employee engagement, and poor management practices significantly contribute to the stagnation of governmental institutions. However, Robbins’ theories provide effective strategies for overcoming these challenges by fostering strong leadership, improving communication, and enhancing motivation through structured organizational policies. The results suggest that implementing Robbins’ frameworks can lead to a more efficient, accountable, and responsive administration, ultimately strengthening state institutions. The study concludes that integrating advanced organizational behavior principles into public administration can be a transformative approach to improving Afghanistan’s governance, promoting institutional stability, and driving long-term state development. By adopting these theoretical insights, policymakers can enhance decision-making processes and create a more resilient and effective bureaucratic system.